The Social Importance And Spiritual Factors Of Ensuring The Balance Of Social Environment And Healthy Lifestyle (Texas Journal of Multidisciplinary Studies, 2025)
In the article has been analyzed the social importance and spiritual factors of ensuring the balance of social environment and healthy lifestyle and also showed forms his own healthy lifestyle in the existing social environment and relies on a healthy body and a healthy mind, he will achieve his own longevity along with being a socially active person as well.